(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
The article the emergence of new concepts and requirements in the sustainable development of the world economy cannot fail to affect such a field as agriculture, which is directly related to nature, but also causes great ecological damage to it.